Maternal preconception and first trimester exposure to PM10 and the risk of oral clefts in offspring: a population-based, case–control study. (31st July 2020) - Liu, Fang-Hua; Dai, Hui-Xu; Gong, Ting-Ting; Zhang, Jia-Yu; Li, Jing; Chen, Zong-Jiao; Li, Li-Li; Chen, Yan-Ling; Liu, Shu; Jiang, Cheng-Zhi; Huang, Yan-Hong; Zhao, Yu-Hong; et al.
Abstract : Background: Current literature describes limited and controversial evidence on the associations between maternal preconception and first trimester exposure to particulate matter with a diameter ≤10 µm (PM10 ) and the risk of oral cleft (OC). Methods: We conducted a case–control study involving 3086 OC cases and 7950 controls, registered in the Maternal and Child Health Certificate Registry in Liaoning Province between 2010 and 2015. PM10 concentrations were obtained from the Environment Protection Bureau. The exposure windows included the 3 months before pregnancy, the first trimester and the individual months. Unconditional logistic regression model was performed to estimate the OR and 95% CI for the association between PM10 exposure and the risk of OC, cleft lip only (CLO), cleft palate only (CPO), and cleft lip and palate (CLP). Results: Maternal PM10 exposure was positively associated with an increased risk for OC during the 3 months preconception (per 10 µg/m 3 increment: OR=1.04, 95% CI 1.01 to 1.07; highest vs lowest quartile: OR=1.23, 95% CI 1.04 to 1.45) and the first trimester (per 10 µg/m 3 increment: OR=1.05, 95% CI 1.02 to 1.08; highest vs lowest quartile: OR=1.37, 95% CI 1.15 to 1.64). Analyses based on individual months presented similar positive associations, particularly in the second month of pregnancy (OR=1.77, 95% CI 1.51 to 2.09) for highest versus lowest quartile. In the subtype analysis, stronger associations were observed for CLO, whereas there was negligible evidence for CPO and CLP. Sensitivity analyses using propensity score matching generated similar findings. Conclusions: Our study provides evidence that PM10 exposure during the 3 months preconception and the first trimester increases the risk of OC.